Traditional serrated adenoma with superficially serrated adenoma: A case treated with endoscopic submucosal dissection with detailed endoscopic observation and pathological study - Momoka Sato; Tomoji Kato; Yu Tezen; Takeshi Hayashi; Toru Matsui; Katsuya Kobayashi; Kenichiro Sekigawa; Ryosuke Tajiri; Hiroshi Mitsui (DEN Open)
Abstract A new subtype of serrated lesions, superficially serrated adenoma (SuSA), has been proposed as a lesion that histopathologically exhibits the morphological features of both conventional adenomas and serrated lesions and is difficult to classify as either one. SuSA has been elucidated to be a precursor lesion of KRAS‐type traditional serrated adenoma. It has also been reported that SuSA may have malignant potential. We report a case treated with endoscopic submucosal dissection and detailed observation. Endoscopy revealed a raised lesion with a two‐tier raised appearance in the sigmoid colon: a tall pinecone‐like reddish structure and flattened whitish elevation on white light imaging. Magnifying narrow‐band imaging revealed conspicuous blood vessels in the pinecone‐like structure and slightly dilated reticular vessels in the flattened area. Crystal violet staining showed that the pinecone‐like structure had a type IVH pit pattern and the flattened area had a stellate to slightly elongated type IIIH pit pattern diagnosed based on Kudo's classification and other pit pattern classification systems. Ki67‐positive cells were distributed in the basal and middle layers of the gland in the flattened elevated area. Genetic analysis results were positive for KRAS mutation and negative for BRAF mutation. Histopathological examination revealed a traditional serrated adenoma in the pinecone‐like structure and SuSA in the adjacent flattened elevated area.